Echocardiographic Profile of Congenital Heart Disease in Shahid Gangalal National Heart Centre - Sharma, Deewakar; KC, Man Bahdur; Rajbhandari, Sujeeb; Maskey, Arun; Malla, Rabi; Rajbhandari, Rajib; Bhatt, Y; Regmi, Shyam; Limbu, Yubaraj (Nepalese Heart Journal, 2004)
Frequency of different types of congenital heart disease in hospital-based set up has not been well assessed in Nepal previously. This study reveals the echocardiographic profile of 1309 congenital heart diseases diagnosed in Shahid Gangalal National Heart Center in between July 2000 to November 2003